New Opportunities in Digital Archaeology: The Use of Low-Cost Photogrammetry for 3D Documentation of Archaeological Objects from Banks Island, NWT - Haukaas, Colleen (Scholarship@Western, 2014)
This thesis investigates the use of low-cost three-dimensional (3D) modelling programs (Agisoft Photoscan and 123D Catch) to create and disseminate digital replicas of archaeological features and artifacts in the context of the Ikaahuk Archaeology Project, a community-based archaeology project on Banks Island, Northwest Territories. It aims to 1) assess the benefits and challenges of low-cost photogrammetry for in-situ documentation of hunter-gatherer archaeological features; 2) determine the usefulness of low-cost photogrammetry for replicating small-scale artifacts in comparison to 3D scanning methods; and 3) explore how Internet media can be used to disseminate 3D models. This thesis demonstrates that low-cost methods of 3D modelling are sufficiently able to replicate many types of archaeological objects, and are accessible due to their low cost, ease of use, and compatibility with online dissemination. As a result low-cost 3D modelling has a promising future in archaeological documentation, conservation, and engagement with non-specialist audiences.